Increased CO2 Relevant to Future Ocean Acidification Alleviates the Sensitivity of a Red Macroalgae to Solar Ultraviolet Irradiance by Modulating the Synergy Between Photosystems II and I - Zhang, Di; Xu, Juntian; Beer, Sven; Beardall, John; Zhou, Cong; Gao, Kunshan (Frontiers in Plant Science, 2021)
While intertidal macroalgae are exposed to drastic changes in solar photosynthetically active (PAR) and ultraviolet radiation (UVR) during a diel cycle, and to ocean acidification (OA) associated with increasing CO2 levels, little is known about their photosynthetic performance under the combined influences of these drivers. In this work, we examined the photoprotective strategies controlling electron flow through photosystems II (PSII) and I (PSI) in response to solar radiation with or without UVR and an elevated CO2 concentration in the intertidal, commercially important, red macroalga Pyropia (previously Porphyra) yeoensis. By using chlorophyll fluorescence techniques, we found that high levels of PAR alone induced photoinhibition of the inter-photosystem electron transport carriers, as evidenced by the increase of chlorophyll fluorescence in both the J- and I-steps of Kautsky curves. In the presence of UVR, photoinduced inhibition was mainly identified in the O2-evolving complex (OEC) and PSII, as evidenced by a significant increase in the variable fluorescence at the K-step (Fk) of Kautsky curves relative to the amplitude of FJ-Fo (Wk) and a decrease of the maximum quantum yield of PSII (Fv/Fm). Such inhibition appeared to ameliorate the function of downstream electron acceptors, protecting PSI from over-reduction. In turn, the stable PSI activity increased the efficiency of cyclic electron transport (CET) around PSI, dissipating excess energy and supplying ATP for CO2 assimilation. When the algal thalli were grown under increased CO2 and OA conditions, the CET activity became further enhanced, which maintained the OEC stability and thus markedly alleviating the UVR-induced photoinhibition. In conclusion, the well-established coordination between PSII and PSI endows P. yeoensis with a highly efficient photochemical performance in response to UVR, especially under the scenario of future increased CO2 levels and OA.